(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2020)
In this scientific article we’ll talk about how to use research methods proactively in the approach to Rural Tourism in Latin America and the Caribbean, to propose how the use of triangulation of research methods can achieve the coresponsibility of social actors in the investigative process, and as a consequence, contribute in the decision making for the development of rural tourism. It is conceived as an articulation of Historicalsocial and economicecological processes that can be interpreted in an interdisciplinary way. The methodical approach is made from the hermeneutic reflection of the constructs: rural tourism, interdisciplinary and qualitative structural research methods and prospective methods and techniques. And the proposal of a combination of research methods for the construction of a methodical that has epistemological and empirical validity for rural tourism. In short: the triangulation of methods must be carried out proactively and creatively, and adapt to the demands of the environment and contextual needs.